BLACK KWETIAU SEBAGAI INOVASI PRODUK TEPUNG BERAS HITAM - Badraningsih Lastariwati, Wahyu Agung Adi Setiawan (Prosiding Pendidikan Teknik Boga Busana, 2020)
This study aims to find recipe, product acceptance in the community as well as test the nutritional content of products by innovating local food products in order to reduce dependence on wheat consumption through black rice substitute rice noodles. The type of research used is R & D (Reaserch and Development) with a 4D development model (Define, Design, Develop, Disseminate). The place and time of the study were the Food Laboratory of the Department of Food and Clothing Engineering Education, Faculty of Engineering, Yogyakarta State University held from February to April 2019. The test material was a sample of each product, while testing instruments were experimental forms, validation forms I and II, panelist sensory test forms, and favorite test forms at the exhibition with data analysis techniques and proximate tests to determine the nutritional content of the product. The results of this study are: 1) The right recipe for black kiwiau products is wheat flour products substituted with black rice flour at 40%. 2) The value of the community's acceptance of black rice products is 3.9 with information very favored, from these data indicating that the product is acceptable to the community. 3) Based on proximate test results black rice has a water content of 54.95gr / 100gr, ash 1.28gr / 100gr, fat 5.46g / 100gr, protein 5.24gr / 100gr, crude fiber 0,2gr / 100gr, carbohydrate 33,1gr / 100gr. Keyword : Local Food Ingredients, Black Rice Flour, Development, Acceptance, Nustrition Test